EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI DI ERA DISRUPTIF PADA KOPERASI PEGAWAI REPUBLIK INDONESIA KOSUKU UNIVERSITAS JENDERAL SOEDIRMAN PURWOKERTO - Aisyah Putri Rizkia; Ira Rachmawati; Lorenzia Ida Ayu Irma Hartiwi; Adi Wiratno (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
Cooperatives are often seen as institutions that still do not maximize the use of technology in their business performance. Utilization of technology, especially information technology can boost the productivity and performance of cooperatives. The KPRI KOSUKU Unsoed Purwokerto has implemented an application system for savings and loans and retail businesses, but it has not been optimal as well as the use of information systems in the preparation of financial reports. This study aims to determine the factors that cause KPRI Kosuku to no longer use the accounting information system in the cooperative's operations. Data obtained from interviews, observations, and documentation. The problems faced by KPRI Kosuku related to the evaluation of accounting information systems are the lack of communication between administrators which is caused by the fact that most of the administrators are employees in other work unit so they cannot monitor system developments, the lack of awareness of administrators in using the system and they are more comfortable using the manual method thus obstruct development system.